Regulasi Usia Minimal Akses Media Sosial Anak di Indonesia: Analisis Yuridis Verifikasi Usia - Zulham Nur Adam (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
The rapid advancement of information technology has intensified children’s use of social media, increasing their exposure to various digital risks, including inappropriate content, cyberbullying, online exploitation, misuse of personal data, and internet addiction. This situation highlights the urgency of regulating a minimum age for social media access that balances children’s freedom of expression with the protection of their best interests. This study analyzes the regulation of age verification for children’s access to social media as stipulated in Government Regulation Number 17 of 2025 on the Governance of Electronic System Operation for Child Protection (PP TUNAS), as well as the gap between legal norms and their implementation. Using a normative legal research method with a descriptive qualitative approach, this study examines statutory regulations, legal doctrines, and relevant secondary sources. The findings indicate that PP TUNAS establishes a foundational legal framework through mandatory age verification and parental consent requirements; however, its effectiveness is limited by the absence of clear technical standards, effective supervision, and concrete audit and sanction mechanisms. Therefore, this study recommends the formulation of detailed technical regulations, the enhancement of parental digital literacy, and the strengthening of inter-agency coordination to ensure effective child protection in the digital environment.